Complex of Models, High-Resolution Schemes and Programs for the Predictive Modeling of Suffocation in Shallow Waters - Sukhinov, Aleksandr; Isayev, Albert; Nikitina, Alla; Chistyakov, Aleksandr; Sumbaev, Vladimir; Semenyakina, Alena (Parallel Computational Technologies, 2017)
The paper covers the development and research of mathematical models of the algal bloom, causing suffocations in shallow waters on the basis of modern information technologies and computational methods, by which the accuracy of predictive modeling of the ecology situation of coastal systems is increased. Developed model takes into account the follows: the water transport; microturbulent diffusion; gravitational sedimentation of pollutants and plankton; nonlinear interaction of plankton populations; biogenic, temperature and oxygen regimes; influence of salinity. The computational accuracy is significantly increased and computational time is decreased at using schemes of high order of accuracy for discretization of the model. The practical significance is the software implementation of the proposed model, the limits and prospects of it practical use are defined. Experimental software was developed based on multiprocessor computer system and intended for mathematical modeling of possible progress scenarios of shallow waters ecosystems on the example of the Azov Sea in the case of suffocation. We used decomposition methods of grid domains in parallel implementation for computationally laborious convection-diffusion problems, taking into account the architecture and parameters of multiprocessor computer system. The advantage of the developed software is also the use of hydrodynamical model including the motion equations in the three coordinate directions.